2008
DOI: 10.1186/1471-2148-8-126
|View full text |Cite
|
Sign up to set email alerts
|

Coral kin aggregations exhibit mixed allogeneic reactions and enhanced fitness during early ontogeny

Abstract: BackgroundAggregated settlement of kin larvae in sessile marine invertebrates may result in a complex array of compatible and incompatible allogeneic responses within each assemblage. Each such aggregate can, therefore, be considered as a distinct self-organizing biological entity representing adaptations that have evolved to maximize the potential benefits of gregarious settlement. However, only sparse information exists on the selective forces and ecological consequences of allogeneic coalescence.ResultsWe s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
107
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(114 citation statements)
references
References 40 publications
(97 reference statements)
6
107
0
1
Order By: Relevance
“…Fusion between allogeneic entities might confer immediate advantage to the chimera by virtue of the increment in size, especially because the latter correlates with fecundity and viability in sessile colonial invertebrates [29]. Greater fitness of multi-chimeras has been confirmed in ascidians [18,30] and corals [8,12], and molecular evidence of chimerism is reported in wild coral populations [7]. However, an important distinction exists in the type of chimeras occurring in the different taxa.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fusion between allogeneic entities might confer immediate advantage to the chimera by virtue of the increment in size, especially because the latter correlates with fecundity and viability in sessile colonial invertebrates [29]. Greater fitness of multi-chimeras has been confirmed in ascidians [18,30] and corals [8,12], and molecular evidence of chimerism is reported in wild coral populations [7]. However, an important distinction exists in the type of chimeras occurring in the different taxa.…”
Section: Discussionmentioning
confidence: 99%
“…In soft corals and colonial hydroids, a window of opportunity was proposed to exist for chimerism during early ontogeny, making it possible only until the complete development of allorecognition [6,9,10]. In cnidarians, chimerism is thus believed to result from a failure to discriminate self from non-self, with few positive outcomes [6,11], except in larger colonies composed of multiple fused entities [8,12]. In ascidians, and possibly bryozoans, frequency of fusion between kin was shown to be positively correlated with relatedness of colonies [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…In CORALZOO, under controlled laboratory settings the consequences of aggregated settlement of kin larvae of S. pistillata were studied (Amar et al, 2008b). When spat came into contact, they either fused, establishing a chimera, or rejected one another.…”
Section: Sexual Propagationmentioning
confidence: 99%
“…Such positive relationships between size and age in maturity and fecundity rates have been reported in some lichenised fungi and corals [93][94][95][96] but see [97]. In this context, somatic fusion could represent a benefit like those suggested by the reports of an increase in fitness following somatic fusion in some fungi or colonial marine invertebrates species [98][99][100]. Interestingly, Amar et al [100] found while studying 544 colonies of a coral species over a period of one year, that growth and survival rates were higher for colonies generated by the fusion of several germ lines, whereas single-germ line colonies had the lowest survival rates.…”
Section: To Fuse: the Evolutionary Benefits Of Fusion Evidence In Botmentioning
confidence: 60%
“…In this context, somatic fusion could represent a benefit like those suggested by the reports of an increase in fitness following somatic fusion in some fungi or colonial marine invertebrates species [98][99][100]. Interestingly, Amar et al [100] found while studying 544 colonies of a coral species over a period of one year, that growth and survival rates were higher for colonies generated by the fusion of several germ lines, whereas single-germ line colonies had the lowest survival rates. In the colonial ascidian B. schlosseri, Carpentier et al [101] observed that chimeras showed a higher fitness than non-chimeras at high-density growth conditions.…”
Section: To Fuse: the Evolutionary Benefits Of Fusion Evidence In Botmentioning
confidence: 93%